Immunohistochemical Expression of E-Cadherin in Normal Oral Mucosa, Precancerous Lesions and Oral Squamous Cell Carcinoma - Bashir, Aneela (International Journal of Pathology, 2022)
Oral cancer is a remarkable component of global cancer burden with significant mortality and morbidity. The present study is designed to assess the Immunohistochemical expression of E-cadherin in tissue samples of diagnosed cases of oral squamous cell carcinoma and oral premalignant lesions and normal oral mucosa. Objective: This study aims to assess the immunohistochemical expression of E-cadherin in tissue samples of diagnosed cases of oral squamous cell carcinoma, OPMLs, and normal oral mucosa Materials and Methods: Total of 60 cases were selected for this Descriptive cross-sectional study which included histologically diagnosed cases of OSCC (n=23), OPMDs (n=23), and Healthy individuals (n=14) as control. Immunohistochemical staining was performed for all cases. Results were analyzed using SPSS version 20. Results: Increased expression of E – cadherin expression was found in samples of normal oral mucosa followed by samples of premalignant and malignant cases. E-cadherin expression was reduced in cases of OPMLs and OSCC as compared to normal oral mucosa. Statistically significant relation was observed while comparing the grade of staining intensity and E-cadherin expression among OSCC cases (p=0.001) and OPML cases (p= 0.01). Conclusion: We concluded that loss of E - cadherin can be used as a tumour marker that could determine the susceptibility of normal and potentially malignant tissues to transform into oral cancers.